Overview of knowledge level clinical students of Faculty of Dentistry Hasanuddin University regarding burning mouth syndrome: Tinjauan tingkat pengetahuan mahasiswa kedokteran gigi Fakultas Kedokteran Gigi Universitas Hasanuddin mengenai sindrom mulut terbakar - Usman, Nur Asmi; Febrianti, Salsa; Mauliana, Anggun; Marlina, Erni; Israyani; Harlina; Yusran, Ali (Makassar Dental Journal PDGI Makassar, 2025)
Burning mouth syndrome (BMS), or glossopyrosis, is a condition characterised by a burning sensation or pain in certain areas of the oral cavity, particularly the tongue, without any changes to the surface of the oral tissue. Some data indicate that BMS suffer-ers are not being treated properly, highlighting the importance of clinical education about BMS for practitioners. This study explo-res the level of knowledge of professional students about BMS. This descriptive analytical cross-sectional study used a ques-tionnaire to collect data, with 74.2% of respondents demonstrating good knowledge of BMS and showing motivation to learn after completing the Clinical Readiness Programme. It was concluded that professional students have a good level of knowledge about BMS, but further research is needed, especially among undergraduate dental students, to increase awareness and knowledge about BMS.